Distance from a cultural model of substance use risk, internalization, and self-stigma in urban Brazil - Henderson, Nicole L.; Dressler, William W.; Pegoraro, Natália Priolli Jora; Falcão, Ana; Pillon, Sandra Cristin (Frontiers in Psychology, 2023)
A cognitive theory of culture, in which culture is encoded in socially distributed cultural models, has proven useful in guiding research over the past forty years. Cultural models exist in two forms. First, there is the shared model upon which individuals within a social group agree. Second, there is the individual version of that model that is modified by personal experience. The integration of cultural models and personal models to produce individual representations of salient cultural domains has been investigated largely through case studies. In this paper, we examine this process and its implications in a study of the distribution of cultural models of the risk of substance use/misuse in a mid-size Brazilian city. In previous research we documented a shared and rather nonspecific cultural model of substance use risk among a general population sample of young adults. Here we examine how this model is re-configured among persons under treatment for substance use/misuse. Overall persons under treatment aggregate risk factors to a greater extent than the general population. Using a cultural distance metric, we find that the more distal persons under treatment are in their ratings of risk factors as influential from the general population configuration, the lower their self-stigma regarding substance use. These findings add an additional perspective on the relationship of culture and the individual.